Views of the Future of Partners of People with Multiple Sclerosis Who Attended a Lifestyle Modification Workshop: A Qualitative Analysis of Perspectives and Experiences - Neate, Sandra L. (Int J Environ Res Public Health, 2020)
People with multiple sclerosis (PwMS) often experience uncertainty and fear about their futures. Partners of PwMS may share their concerns and experience fears about their own futures, limitations on their lives, ability to work, and becoming a carer. For PwMS, modification of lifestyle-related risk factors has been associated with improved health outcomes. For PwMS who attended residential lifestyle modification workshops (RLMW), sustained improved health outcomes have been demonstrated. Whether improved outcomes for PwMS who engage with lifestyle modification translate to improved partner perceptions of the future, is yet to be explored. We explored the perspectives of partners of PwMS who had attended a RLMW and the impact that the person with MS’s illness and their engagement with lifestyle modification had on their partners’ views of the future. Analysis of 21 semi-structured interviews used a methodology informed by Heidegger’s Interpretive Phenomenology. Three themes emerged: ‘uncertainty’, ‘planning for the future’ and ‘control, empowerment and confidence’. Subthemes included MS and lifestyle modification being a catalyst for positive change; developing a sense of control and empowerment; and hope, optimism and positivity. Lifestyle modification may provide benefits, not only to PwMS, but also to their partners, and should be considered part of mainstream management of MS.